Interface induce growth of intermediate layer for bandgap engineering insights into photoelectrochemical water splitting - Zhang, Jian (Sci Rep, 2016)
A model of interface induction for interlayer growing is proposed for bandgap engineering insights into photocatalysis. In the interface of CdS/ZnS core/shell nanorods, a lamellar solid solution intermediate with uniform thickness and high crystallinity was formed under interface induction process. Merged the novel charge carrier transfer layer, the photocurrent of the core/shell/shell nanorod (css-NR) array was significantly improved to 14.0 mA cm(−2) at 0.0 V vs. SCE, nearly 8 times higher than that of the perfect CdS counterpart and incident photon to electron conversion efficiency (IPCE) values above 50% under AM 1.5G irradiation. In addition, this array photoelectrode showed excellent photocatalytic stability over 6000 s. These results suggest that the CdS/Zn(1−x)Cd(x)S/ZnS css-NR array photoelectrode provides a scalable charge carrier transfer channel, as well as durability, and therefore is promising to be a large-area nanostructured CdS-based photoanodes in photoelectrochemical (PEC) water splitting system.